Śmiech, komizm, śmiechoterapia - Wojtaszak, Katarzyna (eBooki.com.pl, 2014)
The subject of the artcle is laughter therapy and opportunities of using humor to promote health and wellness. The first part refers to the phenomenon of laughter and its history, from antiquity to the modern times. The following sections describe the benefits of laughter and methods of using laughter theraphy in working with adults and children. The last part focuses on humor and comedy as the simplest ways to use laughter in everyday life.
Keywords: laughter; humor; laughter therapy; comedy; wellbeing